Impact of entrepreneurship education on the entrepreneurial intention of university students in Latin America (2023)
The correlation between entrepreneurship education and entrepreneurial intention is neither clear nor conclusive. While some studies show a positive correlation between entrepreneurship education and entrepreneurship, others confirm contradictory results. To contribute to the understanding of the relationship between entrepreneurship education and entrepreneurial intention and to contribute to the literature on this topic in Latin America, this research aimed to determine the influence of entrepreneurship education on the entrepreneurial intention of students from five Latin American universities. The type of research is quantitative, cross-sectional, and explanatory. To carry out the study, a questionnaire was applied to 1213 students from five universities in Colombia, Ecuador, Mexico, and Peru. The sample size was determined with a probabilistic design, and the sample was collected randomly by convenience. The Chi-square test showed a p-value of 0.056 higher than 0.05. Therefore, the null hypothesis indicating that entrepreneurship education is independent of entrepreneurial intention was accepted. Practical and theoretical implications emerge from these findings. While acknowledging the importance of entrepreneurship education, it becomes apparent that supplementary mechanisms enhancing entrepreneurial intentions are essential. The absence of a definitive consensus on the connection between entrepreneurial education and intent emphasizes the need for further exploration.